Multiply and simplify by factoring. Assume that all expressions under radical represent nonnegative numbers.

√28a^11b * √8a^12b^10

Tyoe an exact answer, usinf radicals as needed.

Multiply.

√3 (6√7 - 2√25 =

Simplify your answer. type exact answer, using radicals as needed.

I have try these over and over again and still am getting confused how to get to the answers. Please help. Math is not my best subject in school.

## Answers (1)

√28a^11b * √8a^12b^10

If you examine this, you will see it is really all under one √ so:

= √[(28a^11b)(8a^12b^10)]

= √[(224)(a^23)(b^11)]

= √[(2^5)(7a^23)(b^11)]

= √[(2*2*2*2*2)(7a^23)(b^11)]

= 4√[(2)(7a^22+1)(b^10+1)]

= 4a^11b^5√[(2)(7a)(b)]

= 4a^11b^5√[(2)(7a)(b)]

= 4a^11b^5√(14ab)

It didn't want to show all of the second one so I'm trying again...

√3 (6√7 - 2√25)

= √3 (6√7 - 2√5*5)

= √3 (6√7 - 2*5) ← multiplied -2 by the 5 which resulted from √5*5

= √3 (6√7 - 10)

= 6√21 - 10√3